ZnO nanorods assisted Ni1.1Pt and Co3.9Pt alloy microtube counter electrodes for efficient dye-sensitized solar cells. (1st February 2016) - Wang, Jing; Tang, Qunwei; He, Benlin; Yu, Liangmin; Yang, Peizhi
Graphical abstract: Highlights: Ni1.1 Pt and Co3.9 Pt alloy microtubes are synthesized using ZnO nanorod templates. The microtubes are utilized as CE materials for DSSCs. The electrochemical activities are markedly enhanced in comparison with Pt CE. The DSSC yield an efficiency of 8.29% with Ni1.1 Pt CE. The solar cell creates an efficiency of 7.73% with Co3.9 Pt CE. Abstract: Pt counter electrode (CE) has been a burden for the commercialization of liquid-junction dye-sensitized solar cells (DSSCs). In searching for cost-effective CEs without sacrificing electrochemical activities, here we report the experimental realization of ZnO nanorods assisted Ni1.1 Pt and Co3.9 Pt alloy microtube (MT) CEs by combining a simple electrodeposition deposition on aligned ZnO nanorods and a galvanic displacement reaction. On behalf of the good charge-transfer ability along one-dimensional alloy electrocatalyst and electrocatalytic activity toward liquid electrolyte, the resultant DSSCs with Ni1.1 Pt and Co3.9 Pt MT CEs display promising power conversion efficiencies of 8.29% and 7.73%, yielding 30.6% and 21.7% enhancements, respectively. Similarly importantly, the alloyed CEs are still scalable, other alloyed low-Pt or non-Pt nano/microstructures can also be realized using the method reported here.